Polycystic Kidney Disease and Cancer after Renal Transplantation - Wetmore, James B. (American Society of Nephrology, 2014)
Autosomal dominant polycystic kidney disease (ADPKD), the most common form of polycystic kidney disease (PKD), is a disorder with characteristics of neoplasia. However, it is not known whether renal transplant recipients with PKD have an increased risk of cancer. Data from the Scientific Registry of Transplant Recipients, which contains information on all solid organ transplant recipients in the United States, were linked to 15 population-based cancer registries in the United States. For PKD recipients, we compared overall cancer risk with that in the general population. We also compared cancer incidence in PKD versus non-PKD renal transplant recipients using Poisson regression, and we determined incidence rate ratios (IRRs) adjusted for age, sex, race/ethnicity, dialysis duration, and time since transplantation. The study included 10,166 kidney recipients with PKD and 107,339 without PKD. Cancer incidence in PKD recipients was 1233.6 per 100,000 person-years, 48% higher than expected in the general population (standardized incidence ratio, 1.48; 95% confidence interval [95% CI], 1.37 to 1.60), whereas cancer incidence in non-PKD recipients was 1119.1 per 100,000 person-years. The unadjusted incidence was higher in PKD than in non-PKD recipients (IRR, 1.10; 95% CI, 1.01 to 1.20). However, PKD recipients were older (median age at transplantation, 51 years versus 45 years for non-PKD recipients), and after multivariable adjustment, cancer incidence was lower in PKD recipients than in others (IRR, 0.84; 95% CI, 0.77 to 0.91). The reason for the lower cancer risk in PKD recipients is not known but may relate to biologic characteristics of ADPKD or to cancer risk behaviors associated with ADPKD.